A novel Ce3+ activated Lu3MgAl3SiO12 garnet phosphor for blue chip light-emitting diodes with excellent performance. Issue 4 (4th December 2014) - Shi, Yurong; Zhu, Ge; Mikami, Masayoshi; Shimomura, Yasuo; Wang, Yuhua
Abstract : The design, synthesis, and photoluminescence of a novel Lu3 MgAl3 SiO12 :Ce 3+ garnet phosphor for potential warm-white LED applications are reported. Abstract : A novel Ce 3+ activated Lu3 MgAl3 SiO12 :Ce phosphor was synthesized and found to crystallize in the garnet structure. The crystal structure of the synthesized phosphor has been characterised by X-ray diffraction and Rietveld refinement. Both room and high temperature photoluminescence spectra are utilized to investigate the luminescence properties and crystal field splitting. The high temperature quenching of these phosphors and their quantum efficiency (QE) are also studied using both the prepared YAG:Ce and the commercial YAG:Ce phosphor named P46-y3 as the reference. Upon excitation with blue light, the composition-optimized Lu3 MgAl3 SiO12 :Ce phosphor exhibited strong yellow light with a high QE of 81.2% and better thermal stability than that of the commercial phosphor. The results indicate that the Lu3 MgAl3 SiO12 :Ce phosphor can serve as a candidate for blue chip LEDs.